Legal Protection Framework for Digital Forensic Experts in The Society 5.0 Era - Ramadani, Eko Wahyu; Maksun; Idham, Rido; Fikri, Ziya'ul; Ridwan, Muhammad Kholil (Walisongo Law Review (Walrev), 2025)
This study aims to propose a preventive and responsive legal protection framework for digital forensic experts to ensure legal certainty within the criminal justice system. Digital forensic experts play a strategic role in the evidentiary process of cybercrime cases, but often face legal risks arising from their courtroom testimonies. This research employs a normative juridical method, utilizing both statutory and conceptual approaches. The statutory approach examines relevant legal norms and international standards, while the conceptual approach interprets legal principles related to legal certainty, legal protection, and immunity rights for expert witnesses. The data are analyzed descriptively and analytically from a comparative perspective to identify pertinent international legal principles and to formulate a globally applicable framework for the legal protection of digital forensic experts. The novelty of this study lies in the formulation of a limited legal immunity model that integrates professional standards with the principle of due process of law. This study contributes by developing a new normative framework that strengthens the legal protection of digital forensic experts. The findings indicate that limited immunity rights are essential to safeguarding the independence and objectivity of digital forensic experts, provided their actions comply with internationally recognized procedures and ethical standards. Penelitian ini bertujuan untuk merumuskan kerangka perlindungan hukum yang bersifat preventif dan responsif bagi ahli forensik digital guna menjamin kepastian hukum dalam sistem peradilan pidana. Ahli forensik digital memiliki peran strategis dalam proses pembuktian perkara kejahatan siber, namun kerap menghadapi risiko hukum yang timbul dari kesaksiannya di pengadilan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Pendekatan perundang-undangan digunakan untuk menelaah norma hukum dan standar internasional yang relevan, sedangkan pendekatan konseptual digunakan untuk menafsirkan prinsip-prinsip hukum yang berkaitan dengan kepastian hukum, perlindungan hukum, serta hak imunitas bagi saksi ahli. Data dianalisis secara deskriptif dan analitis dengan perspektif komparatif guna mengidentifikasi prinsip-prinsip hukum internasional yang relevan dan merumuskan kerangka perlindungan hukum bagi ahli forensik digital yang berlaku secara global. Kebaruan penelitian ini terletak pada perumusan model imunitas hukum terbatas yang mengintegrasikan standar profesional dengan prinsip due process of law. Kontribusi penelitian ini adalah pengembangan kerangka normatif baru yang memperkuat perlindungan hukum bagi ahli forensik digital. Hasil penelitian menunjukkan bahwa pemberian hak imunitas hukum terbatas sangat penting untuk menjamin independensi dan objektivitas ahli forensik digital, sepanjang tindakan yang dilakukan tetap sesuai dengan prosedur dan standar etika yang diakui secara internasional. Keywords: Digital Forensic Experts; Due Process of Law; Legal Protection; Limited Legal Immunity; Society 5.0.